2018
DOI: 10.1007/s10461-018-2046-0
|View full text |Cite
|
Sign up to set email alerts
|

An Online Risk Index for the Cross-Sectional Prediction of New HIV Chlamydia, and Gonorrhea Diagnoses Across U.S. Counties and Across Years

Abstract: The present study evaluated the potential use of Twitter data for providing risk indices of STIs. We developed online risk indices (ORIs) based on tweets to predict new HIV, gonorrhea, and chlamydia diagnoses, across U.S. counties and across 5 years. We analyzed over one hundred million tweets from 2009 to 2013 using open-vocabulary techniques and estimated the ORIs for a particular year by entering tweets from the same year into multiple semantic models (one for each year). The ORIs were moderately to strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In total, we collected 628,597 tweets and geotagged about 18% of the collected tweets for the analyses (see Table S1). This percentage is similar to the geotagging rates reported in previous studies [48] , [49] .…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…In total, we collected 628,597 tweets and geotagged about 18% of the collected tweets for the analyses (see Table S1). This percentage is similar to the geotagging rates reported in previous studies [48] , [49] .…”
Section: Methodssupporting
confidence: 91%
“…Tweets, including retweets, are informative about popular topics and conversations within a community. Prior studies have shown that county-level tweets can provide signals for predicting HIV/STI infections [49] , [54] and are associated with attitudes, knowledge, and behaviors of infectious diseases such as Zika across U.S. counties [55] . Therefore, we decided to use county as the unit of analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…sex, drug use, HIV risk) were positively associated with HIV prevalence. Expanding this direction of research, Chan et al [7] created an Online Risk Index (ORI) based on tweets as a signal or proxy of county-level HIV, gonorrhea, and chlamydia rates. In addition to Twitter, Google Trends (google search engine) has also been used as a data source for HIV surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, other topics refer to love and celebrations, like 'romance' and 'raw' (topic 66), or 'birthday' and 'celebrating' (topic 45). More generally, topics refer to issues but have no literal interpretation (for a discussion of this issue) [11].…”
Section: Topic Modelingmentioning
confidence: 99%